Conversion between the local magnitude (ML) and the moment magnitude (Mw) for earthquakes in the Croatian Earthquake Catalogue - Herak, Marijan (Array, 2020)
Based on 153 earthquakes (1959–2020) listed in the Croatian Earthquake Catalogue, a conversion relation was obtained between the local magnitude ML,CR and the corresponding moment magnitude Mw as reported by the global and regional agencies. As errors were present in both variables the York regression was used. The best fit line is given by: MwL = (–0.106 ± 0.122) + (1.002 ± 0.027) ML,CR (coefficient of determination R2 = 0.90). The earthquakes considered occurred in Croatia and the neighbouring regions, and their local magnitudes ML,CR ranged between 3.5 and 6.5. Residual analysis suggests that an artificial positive magnitude shift of up to 0.3 magnitude units may have occurred in the early 1980s, when Wiechert mechanical seismographs were replaced by the instruments with velocity proportional recordings without proper recalibration of the magnitude formula. The slope of the regression close to 1.0 indicates that on the average the faults’ aspect ratio (width/length) is about 1/2.